STRATEGI INOVATIF DALAM PEMBELAJARAN BAHASA SUNDA: DIGITALISASI MATERI AJAR UNTUK GURU SEKOLAH DASAR - Nurjanah, Nunuy; Koswara, Dedi; Nugraha, Haris Santosa; Rukmanah, Hani Siti; Ruslan, Ujang (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2025)
Sundanese language, as part of the richness of local culture, plays an important role in shaping the identity and character of the younger generation, especially in the West Java region. However, its existence now faces serious challenges due to declining student interest and limitations of conventional learning resources. This study aims to analyze innovative strategies in Sundanese language learning through the digitalization of teaching materials in elementary schools. Digitalization is considered a modern approach capable of increasing student engagement, enriching methods of delivering material, and preserving local cultural values through interactive media. This research uses a qualitative approach with a descriptive method. Data were obtained through literature studies and interviews with elementary school teachers. The results show that the use of technology—such as learning applications, audio-visual media, and gamification—can increase students' motivation and understanding of the Sundanese language. However, obstacles such as limited infrastructure, lack of teachers' digital competence, and the scarcity of digital learning resources remain major barriers. Therefore, intensive training for teachers, the development of culturally relevant digital content, and policy support from schools and the government are needed. The digitalization of teaching materials is not only a learning solution but also a strategic means of preserving and actualizing Sundanese culture in the digital era. ABSTRAKBahasa Sunda sebagai bagian dari kekayaan budaya lokal memiliki peran penting dalam membentuk identitas dan karakter generasi muda, khususnya di wilayah Jawa Barat. Namun, eksistensinya kini menghadapi tantangan serius seiring menurunnya minat siswa dan keterbatasan sumber belajar konvensional. Penelitian ini bertujuan menganalisis strategi inovatif dalam pembelajaran Bahasa Sunda melalui digitalisasi materi ajar di sekolah dasar. Digitalisasi dianggap sebagai pendekatan modern yang mampu meningkatkan keterlibatan siswa, memperkaya metode penyampaian materi, serta menjaga nilai-nilai budaya lokal melalui media interaktif. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Data diperoleh melalui studi pustaka dan wawancara dengan guru sekolah dasar. Hasil penelitian menunjukkan bahwa pemanfaatan teknologi—seperti aplikasi pembelajaran, media audio-visual, dan gamifikasi—dapat meningkatkan motivasi dan pemahaman siswa terhadap Bahasa Sunda. Namun, kendala seperti keterbatasan infrastruktur, kurangnya kompetensi digital guru, dan minimnya sumber belajar digital masih menjadi hambatan utama. Oleh karena itu, dibutuhkan pelatihan intensif bagi guru, pengembangan konten digital yang relevan secara budaya, serta dukungan kebijakan dari sekolah dan pemerintah. Digitalisasi materi ajar tidak hanya menjadi solusi pembelajaran, tetapi juga sarana strategis dalam melestarikan dan mengaktualisasikan budaya Sunda di era digital.